2014
DOI: 10.21236/ada607614
|View full text |Cite
|
Sign up to set email alerts
|

Rotorwash Operational Footprint Modeling

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Washington Headquarters Services, Directorate for Information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…For the other two cases, the forces exceed the caution limit, but do not reach the danger zone threshold. This result is in agreement with other works, such as in [15] where the PAXman forces of a V-22 have been computed starting from an experimental outflow survey. This reference involved several configurations of disk loading and it has been shown that higher values of disk loading result in forces that reached a peak of 600 N. In all three cases, after 2R, the force drops quickly.…”
Section: Computations and Safety Considerationssupporting
confidence: 92%
See 2 more Smart Citations
“…For the other two cases, the forces exceed the caution limit, but do not reach the danger zone threshold. This result is in agreement with other works, such as in [15] where the PAXman forces of a V-22 have been computed starting from an experimental outflow survey. This reference involved several configurations of disk loading and it has been shown that higher values of disk loading result in forces that reached a peak of 600 N. In all three cases, after 2R, the force drops quickly.…”
Section: Computations and Safety Considerationssupporting
confidence: 92%
“…It is based on the projection of a crouching 6ft tall person immersed in the outwash. The details of the geometry of the PAXman model are shown in figure 1, as reported in [14] and [15]. To be comparable with the small rotor size, the PAXman height is scaled with the rotor radius for three different full-scale rotors, chosen to represent three different weight categories: light, medium and heavy.…”
Section: Paxman Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The rotor was modelled with two untwisted rectangular blades of circular arc, cambered airfoil sections. The radius of the blade, chord, aspect ratio, and solidity were 86 mm, 19.6mm, 4.39, and 0.14, respectively. The blades were set at a collective pitch of 12°, and the results were obtained at a tip Mach number of 0.08.…”
Section: A Trajectories Of the Tip Vortices Of The Lynx Tail Rotor Imentioning
confidence: 99%
“…Then, a momentum-based mathematical model with experimental corrections, including a wall jet theory, and a ground effect correction factor, was described by Kiseilowski and Douglas [17]. The wake contraction was taken into account to quickly evaluate the performance of overlapping and non-overlapping rotor configurations [18,19]. Nevertheless, the drawback of this approach was the limited availability of experimental data for the corrections necessary in the model.…”
Section: Iintroductionmentioning
confidence: 99%